The impact of perceived benefits on cryptocurrency adoption among business travelers: Evidence from MICE tourists in Thailand - Maruding Mareh; Laphassawat Subphonkulanan; Wanamina Bostan Ali; Md Mahmudul Alam; Long Kim (Social Sciences and Humanities Open)
This study investigates the influence of cryptocurrency advantages on MICE (Meetings, Incentives, Conferences, and Exhibitions) tourists' future decisions in Thailand, a prime business travel destination. The research explores how cryptocurrency adoption affects tourists' propensity to use cryptocurrencies in the MICE industry. A sample of 394 MICE tourists’ data was analyzed using Structural Equation Modeling (SEM) via the Mplus program. The results indicate that transaction process (TP), price value (PV), and attitude (AT) significantly impact BTPB, which, in turn, influences future cryptocurrency adoption (FA) while transparency (TR) does not show any significant correlation with business travelers' perceived benefits (BTPB). This study guides travel and tourism stakeholders to enhance cryptocurrency adoption by improving transaction efficiency, security, regulatory clarity, and education, leveraging insights from the Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT) frameworks. This study bridges fintech and sustainable tourism in the MICE industry, offering insights for policymakers and industry leaders to enhance financial systems through cryptocurrency, promoting global sustainable travel practices.